Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/foods11172679
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Durum Wheat Oil in the Preparation of Focaccia: Effects on the Oxidative Stability and Physical and Sensorial Properties

Abstract: Durum wheat oil is an innovative oil that could be considered the “second life” of durum wheat milling by-products. In this study, we proposed the use of this oil in the reformulation of a traditional Italian greased flat bread, namely focaccia, whose typical sensorial features are due to the presence of relevant amounts of oil in its formulation. The chemical, physical, and sensorial features of focaccia with durum wheat oil (DWO) were compared with those of focaccia prepared with olive oil (OO) and sunflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…In the measurements, middle slice of bread (25 mm thickness) was compressed (25% compression ratio) using a 36‐mm diameter cylindrical probe. Crust and crumb colors ( L *, a *, b *) of breads were measured using a colorimeter (HunterLab ColorFlex; HunterLab, Reston, VA, USA), 1 and total color difference (∆ E ) values were calculated by Vurro et al 19 . Total phenolic content and Trolox equivalent antioxidant capacity (TEAC) of breads were respectively determined according to the methods of Beta et al 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In the measurements, middle slice of bread (25 mm thickness) was compressed (25% compression ratio) using a 36‐mm diameter cylindrical probe. Crust and crumb colors ( L *, a *, b *) of breads were measured using a colorimeter (HunterLab ColorFlex; HunterLab, Reston, VA, USA), 1 and total color difference (∆ E ) values were calculated by Vurro et al 19 . Total phenolic content and Trolox equivalent antioxidant capacity (TEAC) of breads were respectively determined according to the methods of Beta et al 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Color analyses of the cookies ( L *: lightness or darkness, a *: redness or greenness, and b *: yellowness or blueness) were conducted with the colorimeter (Color Flex; HunterLab, Reston, VA, USA) and total color difference (∆ E ) values were calculated in accordance with Vurro et al 18 . The diameter ( D ), thickness ( T ), and spread ratio ( D / T ) of cookies were evaluated by AACC method 10‐50D 17 .…”
Section: Methodsmentioning
confidence: 99%
“…45 The ΔE values showed that T10, T20, and T30 led to high color variation as the artichoke bracts replacement increased. According to Vurro et al 46 if ΔE value is higher than 12.0, there is a very evident difference. The ΔE values of T10, T20, and T30 samples were between 19.66-23.68.…”
Section: Physical Chemical and Functional Properties Of Tarhanamentioning
confidence: 97%